Navigating the evolution of marine policy in Panama: Current policies and community responses in the Pearl Islands and Bocas del Toro Archipelagos of Panama. (December 2015) - Spalding, Ana K.; Suman, Daniel O.; Mellado, Maria Eugenia
Abstract: Recent changes in marine policy in Panama are closely related to sustained expansion of the Panamanian economy in the past ten years. Important drivers of economic growth such as the Panama Canal expansion, tourism, and real estate development directly involve marine and coastal areas. Therefore, maintaining the quality of these environments, as well as the sustainability of the human communities that depend on them, calls for the implementation of adequate management and planning policies. In light of a complex history of marine and coastal policy in Panama, current institutional restructuring processes, and a growing recognition of the importance of marine and coastal geographies, the authors aim to document the current status of, and community response to, marine and coastal policy in Panama, analyzed in terms of three important cross-cutting sectors: tourism, fishing, and conservation. To do so, the authors introduce two case studies: one in the Pearl Islands Archipelago and one in Bocas del Toro, each with varying degrees of participation or involvement in each sector, to illustrate the range of adaptations to change occurring in coastal communities. Based on an in-depth policy analysis and the case studies, the authors suggest that there are important administrative and structural gaps in the legislation and institutions that enforce them, as well as a lack of integration across institutions. In particular, the authors highlight the lack of clear marine and coastal property regimes as an obstacle to the implementation of integrative marine policies in Panama. Highlights: This paper is an updated summary of marine and coastal management policy in Panama. There are administrative and structural gaps in marine policy legislation. There is a lack of integration across marine policy institutions. Lack of marine and coastal property regimes limits the use of integrative policies. Coastal communities respond and adapt creatively to current policies.